Safety of octreotide in hospitalized infants. Issue 7 (July 2015) - Testoni, Daniela; Hornik, Christoph P.; Neely, Megan L.; Yang, Qinghong; McMahon, Ann W.; Clark, Reese H.; Smith, P. Brian; ,
Abstract: Background: Octreotide is used off-label in infants for treatment of chylothorax, congenital hyperinsulinism, and gastrointestinal bleeding. The safety profile of octreotide in hospitalized infants has not been described; we sought to fill this information gap. Methods: We identified all infants exposed to at least 1 dose of octreotide from a cohort of 887, 855 infants discharged from 333 neonatal intensive care units managed by the Pediatrix Medical Group between 1997 and 2012. We collected laboratory and clinical information while infants were exposed to octreotide and described the frequency of baseline diagnoses, laboratory abnormalities, and clinical adverse events (AEs). Results: A total of 428 infants received 490 courses of octreotide. The diagnoses most commonly associated with octreotide use were chylothorax (50%), pleural effusion (32%), and hypoglycemia (22%). The most common laboratory AEs that occurred during exposure to octreotide were thrombocytopenia (47/1000 infant-days), hyperkalemia (21/1000 infant-days), and leukocytosis (20/1000 infant-days). Hyperglycemia occurred in 1/1000 infant-days and hypoglycemia in 3/1000 infant-days. Hypotension requiring pressors (12%) was the most common clinical AE that occurred during exposure to octreotide. Necrotizing enterocolitis was observed in 9/490 (2%) courses, and death occurred in 11 (3%) infants during octreotide administration. Conclusion: Relatively few AEs occurred during off-label use of octreotide in this cohort of infants. Additional studies are needed to further evaluate the safety, dosing, and efficacy of this medication in infants. Highlights: The safety profile of octreotide has not been described in infants. We examined diagnoses, laboratory abnormalities, and adverse events in this group. Few adverse events occurred during use of octreotide in our cohort of infants.